SMART CONTRACTS DALAM TRANSAKSI PERDAGANGAN INTERNASIONAL TANTANGAN REGULASI GLOBAL - Andriyani Susilawati; Annie Myranika; Gatot Subroto; Supriadi; M Ali Akbar (CV. Lafadz Jaya, 2026)
Digital transformation in international trade has introduced technological innovation in the form of smart contracts agreements that are automatically executed through computer code on blockchain. This study analyzes the global regulatory challenges faced by smart contracts in the context of international trade transactions. Using normative legal research methods with a comparative approach, this study examines the compatibility of smart contracts with fundamental international legal instruments such as the United Nations Convention on Contracts for the International Sale of Goods (CISG) 1980 and recent developments, namely the UNCITRAL Model Law on Automated Contracting (MLAC) adopted in July 2024. The results show that the MLAC provides legal recognition for contracts in computer code form, but significant challenges remain in terms of jurisdictional fragmentation, cross-border enforcement, system interoperability, and consumer protection. This study recommends regulatory harmonization through the adoption of international standards, development of online dispute resolution (ODR) mechanisms, and a techno-legal approach in formulating smart contract regulatory frameworks that balance innovation and legal certainty.